Phytochemical, pharmacological and industrial application of Chromolaena odorata (Siam weed): An overview based on review of literature - Dharani, P; Kabinesh, V; Krishna moorthi, S; Mathivannan, M; Vijayabhama, M; Ravi, R; Hemalatha, P; Radha, P; Sudha, P; Baranidharan, K; Kumaran, K (Plant Science Today, 2025)
Siam weed (Chromolaena odorata (L.) R.M. King & H. Rob.) of Asteraceae family, a perennial shrub with an invasive character, has been shown potential application in many of scientific communication. On the basis of broader geographical distribution across tropical and subtropical regions, research is mainly concentrated in ten countries of Africa, Asia and Oceania Australia. C. odorata has been largely studied for diverse phytochemical content including flavonoids, terpenoids and phenolic compounds responsible for many of its potential health and industrial application. In present work we reviewed several scientific literature and found antioxidant, anti-inflammatory, wound healing and anti-cancer application of C. odorata. Additionally, environmental applications of C. odorata as a phytoremediation and ecosystem restoration are in agricultural innovations are well established including natural pesticide and soil fertility enhancer. Moreover, several industrial applications including bioenergy and development of sustainable materials are also established. Finally based on balanced summary of available evidence on the ecological challenges and potential as a valuable biological resource for C. odorata and synthesizes current research knowledge that can help in the filling of knowledge gaps and defining of future research directions.